2016
DOI: 10.1002/lary.26130
|View full text |Cite
|
Sign up to set email alerts
|

Early Postnatal NT‐3 Gene Delivery Enhances Hearing Acquisition in the Developmental Period

Abstract: NA Laryngoscope, 126:E379-E385, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
(107 reference statements)
0
1
0
Order By: Relevance
“…Hence, the administration of exogenous neurotrophic factors has been widely studied in animal models of SNHL, showing a pro-survival effect for auditory neurons in models of SNHL [176,237]. A wide number of studies have revealed that BDNF and NT-3 are the most common neurotrophic factors used in animal models of hearing loss [238][239][240][241][242][243][244][245][246][247][248][249][250][251][252][253].…”
Section: Bdnf Protective Effects Against Hearing Lossmentioning
confidence: 99%
“…Hence, the administration of exogenous neurotrophic factors has been widely studied in animal models of SNHL, showing a pro-survival effect for auditory neurons in models of SNHL [176,237]. A wide number of studies have revealed that BDNF and NT-3 are the most common neurotrophic factors used in animal models of hearing loss [238][239][240][241][242][243][244][245][246][247][248][249][250][251][252][253].…”
Section: Bdnf Protective Effects Against Hearing Lossmentioning
confidence: 99%